An Empirical Study for Estimating Ultimate Bearing Capacity of Concrete Small-Pile Cluster in Soft Clays - Suyuti Suyuti; Mukhlis Muslimin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Soft subgrades with shear strength, cu of 10 kPa to 25 kPa are given low bearing capacity and high settlement. Local government has been built infrastructure of embankment such unpaved road on the soft subgrade by using timber and bamboo materials (called “Cerucuk”) are very familiar for Indonesian local people. By developing load capacity of floating pile type, bamboo pile cluster was applied for Tol road in North the Java Island. However, bamboo material limited of life construction inside the soft ground, and exploitation of timber pile was violated environmental issue. Therefore, this research method is developed a new geometrical small - cluster pile by using concrete from local material or Igneus stone such as gravel and sand produced in quarry Ternate Island. Ultimate bearing capacity of single small - cluster pile installation modelled in soft subgrade tank. Then, observed by several block concretes and it is presented by empirical formulae. Finally, the ultimate load capacity of small-pile cluster in soft subgrade is obtained Qu of 15.92 kN and 19.79 kN for observation and calculation, respectively. Rearrange of piles can be increased load capacity of small-cluster pile in soft subgrade as spacing single pile by spacing 5Deq to 3Deq. Mostly load capacity of small-pile clusters should be calculated by using empirical method to provide bearing capacity based on geotechnical rule with laboratory and field soil investigation data and load standard for unpaved roads.